Microchannel-Embedded D-Shaped Photonic Crystal Fiber-Based Highly Sensitive Plasmonic Biosensor - Jannatul Mawa Nijhum; Tanvir Ahmed; Md. Anwar Hossain; Javid Atai; Nguyen Hoang Hai (Applied Sciences, 2022)
An improved design of a D-shaped photonic crystal fiber (PCF)-based refractive index (RI) sensor is proposed that uses the surface plasmon resonance phenomenon. The sensor consists of a large semicircular open channel that is inserted at the upside of the D-shaped PCF. A thin plasmonic sensing layer is deposited on the interior surface of the channel to excite the surface plasmon wave that eliminates the requirement of additional effort to fabricate a well-polished sensing layer of the D-shaped sensor. The sensor’s optical properties are numerically explored by the finite element method. The sensor is optimized to detect the RI of biological and biochemical analytes in the range of 1.33 to 1.44, shows spectral sensitivity as high as 63,000 nm/RIU with a spectral resolution of 1.59 × 10−06 RIU, and maximum amplitude sensitivity of 1439 RIU−1 with a resolution of 6.94 × 10−06 RIU. It is also found that the sensor’s linearity parameter is very high with a large figure of merit of about 839. Additionally, the sensor’s fabrication tolerance is studied by varying its structural parameters. Therefore, high sensing parameters with a wide detection range make this microchannel-based D-shaped PCF sensor an appropriate device for the application of biological and biochemical analyte detection.